Kinetics of the hydration process and rheology of cement pastes containing mechanically activated chalcedonite powder - Spychał, Edyta; Vyšvařil, Martin (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Reducing the amount of Portland clinker in the cement composition is one of the key aspects of the strategy aiming to reduce carbon dioxide emissions. One solution is to use waste materials for this purpose, for example, stone fine powder, especially limestone, basalt, granite, and melaphyre powder. There is insufficient information about the use of chalcedonite powder as an addition in cement or cement composites. Also, there is no precise information about the impact of this material on the particle size and the resulting changes in the properties of cement pastes. Therefore, this study investigates how the particle size and amount of chalcedony powder affect the hydration processes and rheological properties of cement pastes. The addition was used at 10%, 20%, and 30% by weight of the cement, with grain sizes up to 10 µm, 20 µm, and 36 µm, respectively. The hydration kinetics of the pastes were assessed based on calorimetric measurements, supplemented by DTA-TG analysis and mechanical properties tests. Additionally, the rheological properties were determined. The study demonstrated that chalcedony powder affects the tested parameters to varying degrees. In rheological research, the cement paste containing the largest grain size (CHP36) chalcedonite powder showed the most similar properties to the CEM cement paste (without the addition). In contrast, the pastes modified with chalcedonite powder, in which the cement was replaced by 10% of the additive, exhibited the highest amount of cumulative heat. In terms of 28-day compressive strength, the materials containing CHP20 powder demonstrated the most similar properties to the reference paste, without the addition.